Moravský kras a okolí / Moravian Karst and its Environs - Balák, Ivan; Hofmann, Eduard; Svobodová, Hana; Durna, Radek; Kolejka, Jaromír (Masaryk University Press, 2022)
Title in English: Moravian Karst and its Environs: Atlas for field work and outdoor activities. The atlas The Moravian Karst and its Environs includes an area which is used for outdoor activities by a number of schools not only from the Czech Republic, of all types and grades. The needs of fieldwork in the frame of teacher education at PdF MU were taken into consideration. The mission of the Atlas is to raise the desire to learn something new about processes which shaped and still shape the landscape of the Moravian Karst and its environs. The Atlas itself is composed of two parts. The first part is formed of thematically oriented maps with a scale of 1 : 160,000 and 1 : 400,000. It contains an overall overview of the chosen area and a description of its basic natural and cultural characteristics. The second part comprises detailed maps with a 1 : 20,000 scale which contain a huge amount of additional information. Its main goal is to support its users in their exploration of areas they choose from maps and thus help them to explore points of interest which are depicted by cartographic symbols.